Problem-Based Learning with Video Media on Students’ Learning Outcomes in Electrical Power Basics: A Quasi-Experimental Study - Noviani; Hasan Maksum; Dony Novaliedry (Journal for Lesson and Learning Studies, 2025)
Effective learning should be designed to be active, contextual, and student-centered in order to foster both conceptual understanding and procedural skills. However, teacher-centered instructional practices often limit students’ active participation, resulting in low retention and difficulties in applying theory to practical contexts. This study aims to analyze and examine the effect of the Problem-Based Learning (PBL) model supported by video media on students’ learning outcomes in the Basic Electrical Engineering course. The study employed a quasi-experimental design with a nonequivalent control group, involving 60 tenth-grade students from the Electrical Power Installation program who were divided into an experimental group and a control group. Data were collected using a multiple-choice achievement test that had undergone validity and reliability testing and were analyzed using an independent samples t-test to identify differences in posttest mean scores. The results indicated that the group taught through video-assisted PBL achieved significantly higher posttest scores than the group taught using conventional lecture methods, with a moderate effect size. These findings suggest that integrating PBL with structured video media effectively enhances learning outcomes in vocational education. The study implies the importance of implementing problem-based instructional strategies supported by visual media to strengthen instructional quality and promote innovation in vocational learning environments.